Synthesis of 3, 4‐Fused γ‐Lactone‐γ‐Lactam Bicyclic Moieties as Multifunctional Synthons for Bioactive Molecules. (2nd June 2015) - Shaameri, Zurina; Azib, Nur Aini; Mohamat, Mohd Fazli; Hamzah, Ahmad Sazali
Abstract : A short approach for the synthesis of 3, 4‐fused γ‐lactone‐γ‐lactam bicyclic systems (1 ) in diastereomeric mixtures from chiralD ‐alanine methyl ester hydrochloride is described. The key step towardslactonisation is the reduction of the carbonyl ketone of the 5 R ‐configured 3, 5‐dimethylpyrrolidine‐2, 4‐dione diastereomers (8 ) via sodium borohydride in the presence ofhydrochloric acid . With the presence of ethyl acetyl functionality at C3‐position, ester hydrolysis of8 occurred concomitantly with keto reduction leading tolactonisation and eventually affording the anticipated (3 S, 4 S, 5R ), (3 R, 4 R, 5R ), (3 R, 4 S, 5R ) and (3 S, 4 R, 5R ) bicyclic moieties. The formation of the fused systems was confirmed by mass spectroscopy (MS) andnuclear magnetic resonance (NMR) analyses. Abstract :